99mTc‐HMPAO‐leukocyte scintigraphy for diagnosis and therapy monitoring of skull base osteomyelitis. Issue 3 (14th May 2018) - Rozenblum‐Beddok, Laura; Verillaud, Benjamin; Paycha, Frédéric; Vironneau, Pierre; Abulizi, Mukedaisi; Benada, Abdel; Cross, Tumatarii; El‐Deeb, Ghada; Vodovar, Nicolas; Peretti, Ilana; Herman, Philippe; Sarda‐Mantel, Laure
Abstract : Objective: Skull base osteomyelitis (SBO) is a rare but life‐threatening disease observed in elderly diabetic patients, with high risk of recurrence and difficult therapeutic management. The diagnosis is ascertained from a set of clinical, biological, and imaging findings. CT and MRI allow initial diagnosis, but are not accurate to affirm healing at the end of therapy. 99mTc‐HMPAO‐Leucocyte Scintigraphy (LS) is highly sensitive and specific for the detection of infection. The aim of this study was to evaluate LS i) for initial diagnosis, and ii) to confirm healing at the end of antibiotherapy in SBO. Study design: We retrospectively reviewed from November 2011 to September 2015 all patients with confirmed SBO who underwent LS twice, at diagnosis and at the end of antibiotic therapy in our nuclear medicine department (n = 27). Methods: Clinical, biological, CT, LS, and follow‐up data were recorded in all patients. LS images (planar and tomographic performed 4 hours and 24 hours after intravenous injection of autologous Tc‐99m‐HMPAO‐leucocytes) were visually assessed and quantified. Results: At initial diagnosis, 25 of 27 patients had a positive LS. At the end of antibiotic therapy (3 ± 1 months duration), 26 of 27 patients had a negative LS. During subsequent follow‐up (= or >6 months), the disease recurred in four patients including three with a negative postantibiotherapy LS scan. Conclusion: In this retrospective study, LS was powerful for initial diagnostic of SBO and for healing assessment at the end of antibiotic therapy. We conclude it is a useful technique for therapeutic monitoring of SBO. Level of Evidence: 4